Vicious circle in power sector - Thanju, Jeevan P (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Not available. DOI: 10.3126/hn.v7i0.4221 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 8 Uploaded Date: 28 January, 2010